Remodelamento ventricular direito e esquerdo em fase precoce ao infarto agudo do miocárdio: uma visão proteômica - Maretto, Gabriella Xavier (2017)
Post-infarction ventricular remodeling is a dynamic and complex process that occurs in response to myocardial damage. However, little is known about changes in the proteome of the cardiac chambers in the early phase remodeling after infarction and in the development of heart failure (IM-CI). The objective of this study was to evaluate protein changes in right ventricular (RV) and left ventricular (LV) remodeling of rats with signs of heart failure, 7 days after infarction, using proteomic analysis - comparative DIGE and mass spectrometry. The infarction was obtained by occlusion of the left coronary artery and heart failure confirmed by the analysis of the left ventricular enddiastolic pressure ≥ 15 mmHg; increased lung mass / body mass ratio and presence of RV hypertrophy, with concomitant reduction in LV contractility and relaxation indexes. The quantitative analysis revealed differences in intensity / expression of 20 proteins in the RV and 11 in the LV of the infarcted animals with signs of heart failure (p <0.05), 14 of these proteins were identified by MALDI-TOF / TOF. Changes were detected in proteins related to energy metabolism (carbohydrates, lipids, amino acids and oxidative phosphorylation), heat shock proteins, muscle contraction and structural proteins and diverse functions.